PENYUSUNAN BANGUNAN BATA CANDI GAYATRI (KAJIAN TEKNOLOGI BERDASARKAN ANALISIS LABORATORIUM) - Astiti, Ni Komang Ayu (Berkala Arkeologi, 2003)
The results of laboratory analysis prove that in ancient times, the construction of the Gayatri Temple had paid attention to the construction and quality of building raw materials to obtain a temple building that was strong, sturdy and resistant to disturbances due to environmental factors. The strength of the temple building which uses the main material of red brick depends on the quality of the raw material and the technology of its manufacture. The red brick used in the Gayatri temple building contains high silicate (SiO2) and lime (CaC03) compounds. The combination of these two compounds makes the red bricks strong and sturdy, if the opposite happens, the red bricks become very brittle and break easily.